Tes Sederhana Deteksi Neuropati Pada Pasien Diabetes Mellitus Tipe 2 : Studi Literatur - Halbina Famung Halmar; Yuliana Syam; Saldy Yusuf (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background :One of the microvascular complications of Diabetes Mellitus (DM) causes loss of sensation in the peripheral area, especially the legs. If the loss of sensation not detected earlier, it will be at risk for foot injury. The method that has been studied requires special tools, used by trained personnel and expensive cost. Therefore, the purpose of this literature review was to find simple test that can be used by the community, easy, effective and inexpensive for detecting the neuropathy. Methode : the Data was being searched since 2013 to 2018 used 3 data bases (Pubmed, ScienceDirect, Google scholar) which published internationally and in English. Result :There were 10 articles used in this literature review. There were four tests to detect diabetic neuropathy. SUDOSCAN is a test that does not require special preparation and can be used by people who are not trained, it takes 2 minutes. NEUROPAD can be done by non-professional staff, the patient feels comfortable during the test and it takes 10 minutes. NerveCheck takes 9 minutes to 13 minutes and is easy to use. The simplest test is Ipswich Touch Test (IpTT), non-professionals can do this easily, fast (1-2 seconds), and without requiring fees. Conclusions: Ipswich Touch Test (IpTT) is an easy test, effective, does not require tools and it can be used by the general public. IpTT can be used to detect neuropathy in hospitals and homes.